The what and how of questionnaires in second language research to cope with technological advances: design, administration, and processing - Elih Sutisna Yanto; Kusrin (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2023)
In their book, Zoltán Dornyei and Jean-Marc Dewaele's Questionnaires in Second Language Research offers a comprehensive, reader-friendly overview of the theory of questionnaire design, administration, and processing, made accessible with a detailed how-to guide and concrete, real-world applications. This third edition has been thoroughly revised to reflect advancements in the field and includes recent case studies focusing on the considerations, challenges, and opportunities of online questionnaires at all research stages. In this book, the authors also guide readers on how to use the IRIS database and how to clean, process, and analyze questionnaire data before reporting findings. This is an invaluable resource for SLA, applied linguistics, psychology, and education students and researchers interested in understanding and conducting both qualitative and quantitative questionnaire-based L2 research. This review is a memorial for Zoltán Dornyei, who passed away on June 10, 2022.